A new genus and species of Australian Tanypodinae (Diptera: Chironomidae) tolerant to mine waste - Cranston, Peter S. (Zootaxa, 2017)
For over 25 years an undescribed Tanypodinae (Diptera: Chironomidae) has been known to dominate the lotic invertebrate assemblage associated with long-term polluting mine adits in Captains Flat, on the Molonglo River, southern New South Wales, Australia. Although known in all life stages, it has been impossible to allocate the species to any described genus. Renewed interest in the taxonomy of the Tanypodinae, particularly associated with molecular investigations and pollution indicator status warrants formal description. All stages conform to tribe Pentaneurini, but each life stage differs in morphological resemblance. Yarrhpelopia Cranston gen. n. is proposed for the taxon previously referred to under the informal code name of ’genus A’. The genus name derives from south-east Australian aboriginal word yarrh, in recognition of its core distribution and presence in flowing waters. A single species, A. norrisi Cranston sp. n., is described, acknowledging the late Professor Richard Norris, an influential Australian limnologist. Larvae dominate the benthos immediately adjacent to mine adits that continue to leach heavy metals (zinc, cadmium, copper and lead) into downstream sediments. A wider distribution includes cleaner near pristine, eastern Australian rivers between 30° and 42°S, but these records are excluded from the type series pending molecular insights into species limits.